Síntese e caracterização de Filmes LSM/SDC como catodos compósitos para células a combustível de óxido sólido - Melo, Marcus Antônio de Freitas (2010)
The study of the strontium-doped lanthanum manganites in the form of films covers a large area of technological applications, such as ceramics semiconductors and solid oxide fuel cell cathode. Strontium-doped lanthanum manganite and samarium-doped ceria has been used as composite cathode of solid oxide fuel cells (SOFCs) because of its excellent performance in electronic and ionic conductivity. In this work, we produced films of the cathode LSM / SDC on yttria stabilized zirconia (YSZ) electrolytes. La0.8Sr0.2MnO3 (LSM) and Ce0.8Sm0.2O1.9 (SDC) powders were synthesized by a synthesis route similar to the Pechini method, in which the gelatin replaced the ethylene glycol as polymerizing agent. Precursor powders of LSM and SDC phases were calcined at 900 oC. In the step of films production were prepared suspensions of the LSM and SDC powderswith addition of ethyl cellulose as a pore-forming agent. The ceramic suspensions were deposited on YSZ electrolyte using the spin coating method. After sintering to 1150 °C for 4 h the films were characterized by XRD and SEM. The film with 10 wt.% ethyl cellulose presented porous and strongly adhered to the YSZ substrate